Caracterización de los residuos sólidos municipales y no municipales generados en el asentamiento humano Nadine Heredia, San Juan Bautista, 2022 - Dasilva Vasquez, Dayane (2022)
The purpose of this research work was to study the characterization of municipal and non-municipal solid waste generated in the Nadine Heredia Human Settlement, as well as to carry out the quantification of waste, calculation of density and determination of per capita generation; In addition to recording the opinion of the inhabitants on the generation, segregation and disposal of municipal and nonmunicipal solid waste in their community, in order to know the amount and types of waste that are generated, and thus improve their segregation and disposal. Through the analysis and processing of the information collected from the inhabitants of the Nadine Heredia Human Settlement, a total value of 2,149,500 kg has been obtained from the quantification of waste, with organic matter being the largest waste generated with a value of 1,203,310 kg. , followed by plastic with 430,220 kg, paper with 255,700 kg, cardboard with 169,840 kg, metal with 50,650 kg, and glass with 39,780 kg.